Sci—Thur AM: YIS ‐ 01: Dosimetric Analysis of Respiratory Induced Cardiac Intrafraction Motion in Left‐sided Breast Cancer Radiotherapy. Issue 8 (30th November 2016) - El‐Sherif, O; Xhaferllari, I; Patrick, J; Yu, E; Gaede, S
Abstract : Introduction: Long‐term cardiac side effects in left‐sided breast cancer patients (BREL) after post‐operative radiotherapy has become one of the most debated issues in radiation oncology. Through breathing‐adapted radiotherapy the volume of the heart exposed to radiation can be significantly reduced by delivering the radiation only at the end of inspiration phase of the respiratory cycle, this is referred to as inspiration gating (IG). The purpose of this study is to quantify the potential reduction in cardiac exposure during IG compared to conventional BREL radiotherapy and to assess the dosimetric impact of cardiac motion due to natural breathing. Methods: 24 BREL patients treated with tangential parallel opposed photon beams were included in this study. All patients received a standard fast helical planning CT (FH‐CT) and a 4D‐CT. Treatment plans were created on the FH‐CT using a clinical treatment planning system. The original treatment plan was then superimposed onto the end of inspiration CT and all 10 phases of the 4D‐CT to quantify the dosimetric impact of respiratory motion and IG through 4D dose accumulation. Results: Through IG the mean dose to the heart, left ventricle, and left anterior descending artery (LAD) can be reduced in comparison to the clinical standard BREL treatment by as much as 8.39%, 10.11%, and 13.71% respectively ( p < 0.05 ). Conclusion: Failure to account for respiratory motion can lead to under or overestimation in the calculated DVH for the heart, and it's sub‐structures. IG can reduce cardiac exposure especially to the LAD during BREL radiotherapy.